Talent Classification: Recognizing and Developing Personal Potential Optimally at Tarsisius Vireta High School - Januaviani, Trisha Magdalena Adelheid; Kalfin, Kalfin; Arifin, Alicia; Gunawan, Naftali Brigitta (Research Collaboration Community (Rescollacom), 2024)
Knowing students' talents and interests from an early age is very important to help them develop their potential more effectively. Every individual is unique, and the process of identifying talents and interests requires patience and a deep understanding of the student. With a good approach, we can help students develop their potential optimally. This research aims to explore the potential of students at Tarsisius Vireta High School using a talent classification approach. In the educational context, recognizing and developing students' potential is the key to achieving personal success and positive contributions to society. The research method used is qualitative with data collection techniques through questionnaires given before (Pre Test) and after (Post Test) the seminar given to students. The data obtained becomes evaluation material in determining how much students know the talents each student has. Based on the results of the analysis, it was found that there was a significant increase in students' awareness of their talents and interests, as well as their ability to identify and categorize talents. With a deeper understanding of students' potential, it is hoped that education at Tarsisius Vireta High School can be more optimal in developing students' talents and interests, so that they are ready to face the future with confidence and honed abilities.